Roles of Lymphocyte Kv1.3-Channels in the Pathogenesis of Renal Diseases and Novel Therapeutic Implications of Targeting the Channels - Itsuro Kazama (Hindawi Limited, 2015)
Delayed rectifier K+-channels (Kv1.3) are predominantly expressed in T lymphocytes. Based on patch-clamp studies, the channels play crucial roles in facilitating the calcium influx necessary to trigger lymphocyte activation and proliferation. Using selective channel inhibitors in experimental animal models, in vivo studies then revealed the clinically relevant relationship between the channel expression and the pathogenesis of autoimmune diseases. In renal diseases, in which "chronic inflammation" or "the overstimulation of cellular immunity" is responsible for the pathogenesis, the overexpression of Kv1.3-channels in lymphocytes promotes their cellular proliferation and thus contributes to the progression of tubulointerstitial fibrosis. We recently demonstrated that benidipine, a potent dihydropyridine calcium channel blocker, which also strongly and persistently inhibits the lymphocyte Kv1.3-channel currents, suppressed the proliferation of kidney lymphocytes and actually ameliorated the progression of renal fibrosis. Based on the recent in vitro evidence that revealed the pharmacological properties of the channels, the most recent studies have revealed novel therapeutic implications of targeting the lymphocyte Kv1.3-channels for the treatment of renal diseases.